Advokasi Kawasan Tanpa Rokok (KTR) the Indonesia Tobacco Control Research Network (ITCRN) Kabupaten Lebak - Rusyanti, Siti; Rokayah, Yayah; Aulia, Annisa Rahma Nur; Ratnasari, Dini Saptika; Bakhtiar, Bakhtiar; Tilawah, Nining; Ahsan, Abdillah (Universitas Malahayati Lampung, 2025)
ABSTRACT Breathing clean, fresh air without exposure to cigarette smoke is a fundamental human right. The WHO states that diseases caused by exposure to cigarette smoke are a global health problem. 70% of smoking-related deaths occur in developing countries, including Indonesia. Advocacy for Smoke-Free Areas is crucial, given the increasing prevalence of smoking among all groups, including adolescents, globally, nationally, and regionally. Implementing existing regulations is crucial. Various obstacles are often encountered, so support from various parties is essential, including stakeholders, policymakers, and all levels of society. The government aims for all regencies/cities in Indonesia to have regulations on Smoke-Free Areas (KTR). Lebak Regency already has Regional Regulation (Perda) No. 3 of 2023 on KTR, but this KTR Regulation needs to be refined with the establishment of a KTR Task Force and a Regent's Regulation (Perbup). Full cross-sectoral support has not been provided. Currently, only two regional government agencies (SKPD) in Lebak Regency have implemented designated smoking areas: the Health Office and the Education Office, which are open-air gazebos. The cigarette market has also expanded with the introduction of e-cigarettes, a type of kretek cigarette, and therefore the advertising/advertising ban also applies. The Lebak Regency Non-Smoking Area Advocacy Team has carried out activities according to the established plan, including an audience with the Regional Assistant for Economic and Development, advocacy, socialization of the Non-Smoking Area Regional Regulation and the inauguration of the Non-Smoking Area Task Force in Lebak Regency, a podcast about Non-Smoking Areas (KTR), an article competition on the dangers of smoking and a Non-Smoking Area Banner Design Competition, as well as socialization of Non-Smoking Areas (KTR) and the dangers of smoking at the Car Free Day event in Rangkasbitung City, Lebak Regency, Banten Province. Keywords: Smoke-Free Areas (KTR). ABSTRAK WHO menyatakan bahwa penyakit yang disebabkan oleh paparan asap rokok menjadi masalah kesehatan dunia. 70% kematian karena merokok tersebut terjadi di negara berkembang, termasuk Indonesia. Advokasi Kawasan Tanpa Rokok sangat krusial untuk diterapkan mengingat perilaku merokok sudah semakin meluas pada seluruh kelompok masyarakat termasuk pada remaja, baik secara global, nasional, maupun regional. Implementasi regulasi yang sudah ada sangat penting dilakukan. Berbagai kendala sering kali ditemukan, sehingga support dari berbagai pihak sangat diperlukan mulai dari pemangku kepentingan, pembuat kebijakan, dan seluruh unsur lapisan masyarakat. Pemerintah mempunyai target bahwa seluruh kabupaten/kota di Indonesia memiliki peraturan tentang Kawasan Tanpa Rokok (KTR). Kabupaten Lebak sudah memiliki Peraturan Daerah (Perda) KTR nomor 3 Tahun 2023, namum Perda KTR tersebut harus disempurnakan dengan dibentuknya unsur Satuan Petugas (Satgas) KTR dan Peraturan Bupati (Perbup). Dukungan lintas sektor belum diberikan sepenuhnya. Saat ini baru terdapat 2 SKPD di Kabupaten Lebak yang sudah menerapkan ruang khusus merokok, yaitu Dinas Kesehatan dan Dinas Pendidikan, berupa gajebo di ruang terbuka. Produk rokok sudah semakin berkembang dengan adanya rokok elektrik, rokok jenis ini sudah termasuk ke dalam jenis rokok kretek, sehingga larangan iklan/reklame pun berlaku sama Tim Advokasi KTR Kabupaten Lebak telah melaksanakan aktivitas sesuai dengan rencana yang telah ditetapkan, terdiri dari audiensi dengan Asisten Daerah Perekonomian dan Pembangunan, Advokasi, Sosialisasi Perda KTR dan Pengukuhan Tim Satgas KTR di Kabupaten Lebak, Podcast tentang KTR, Lomba Artikel tentang bahaya merokok dan Lomba Desain Spanduk KTR, serta sosialisasi KTR dan bahaya rokok pada event Car Free Day di Kota Rangkasbitung Kabupaten Lebak Provinsi Banten. Kata Kunci: Kawasan Tanpa Rokok (KTR)